Permissive Attitude Towards Premarital Sex Among University Students In Malaysia - Does Childhood Abuse Play A Role? - Sharifah Najwa Syed Mohamad; Khairatul Nainey Kamaruddin; Nur Amirah Shibraumalisi; Fadzilah Mohamad; Syifa’ Mohd Azlan; Rahima Dahlan; Irmi Zarina Ismail; Hayati Kadir Shahar (Malaysian Journal of Medical and Health Sciences, 2024)
Indexed by Scopus/MyCite